"We're not going to say it's suffering; we're going to say it's an experience": The lived experience of maternal caregivers in pediatric kidney transplantation. (13th September 2016) - Mantulak, Andrew; Nicholas, David B.
ABSTRACT: Advances in the surgical and immunological aspects of pediatric kidney transplantation have resulted in significant improvements in long-term outcome and survival rates. However, there continues to be a negative impact reported on overall family functioning despite the reported good health and quality of life for the transplanted child. This research utilizes a phenomenological approach to examine the lived experiences of seven mothers of children who had undergone kidney transplantation. Findings of the study illuminate that the experience of mothering in the context of pediatric kidney transplantation is reflected in (1) the significance of relationships to the experience of self; (2) the lived experience of time; and (3) opportunities for growth and personal development. This research identifies that, while maternal caregiving in this context is fraught with challenges, there are opportunities for the development of skills and personal growth within the experience. By embracing a strength-based perspective, social work is well positioned to offer support for maternal meaning-making and adjustment during times of stress and uncertainty.